The Characteristics of Trademark Management and Its Role in Achieving Competitive Advantage: Applied Study- Qatar Telecommunication Company - Al-Abbasi, Hassan Ali; Adaileh, Ali Mohammad (Jordan Journal of Business Administration, 2023)
This study aims to examine the characteristics of trademark management and its role in achieving competitive advantage at Qatar Telecommunication Company "Ooredoo". To meet this objective, a quantitative descriptive approach was adopted through using a questionnaire as the main tool for data collection. A random sample of (340) participants was randomly recruited from the company's employees. The questionnaires were electronically distributed via the Google Form program. About (311) questionnaires were completed which represented (91%) of all questionnaires. The data was statistically analyzed. The results revealed that there is a significant impact of the characteristics of trademark management on achieving competitive advantage in the company. Furthermore, the impact of every dimension of the competitive advantage represented in product quality, response to customers, creativity, innovation and efficiency was statistically significant. The findings also showed that the characteristics of the company's brand management and competitive advantage are applied at a high level. The study recommends that the company proceeds in studying the changes in the market and tools to achieve competitive advantage, identifying future opportunities to utilize them to achieve this advantage, besides developing technology to improve services. The study also suggests conducting future research that shows the relationship of the brand with variables, such as customer satisfaction, the degree of trust in the brand, the phenomenon of brand imitation and its impact on the reputation of the original brand and ways to combat this phenomenon.